Factors That Affect The Event Of Hipertension In Elderly In The Herlang Puskesmas Working Area - Endang; Safruddin; Muriyati (Comprehensive Health Care, 2019)
According to data from the 2014 Bulukumba health service, there were 6,355 people with hypertension and in 2016 there were 10,430 people and there were 11,714 blood pressure measurements, this hypertension increased every year. The purpose of this study is to know the factors that influence the incidence of hypertension in the elderly. Research design with 'Cross-sectional' 'the population in this study were elderly in the working area of ​​the Herlang Public Health Center many as 120 respondents, the sample in this study amounted to 62 respondents take by using a Multivariate formula, data analysis using the result of this study indicates using the chi-square test with the value (p = 0.027), which men that there is an effect of smoking on the incidence of hypertension. And the consumption of salt with values ​​(p = 0.012), which means there is an influence of salt consumption on the incidence of hypertension and lack of physical activity obtained values ​​(p = 0.012) which means there is an influence on the incidence of hypertension in the elderly. The conclusion of this research is' there is an influence between smoking, consuming salts and lack of physical activity in the working area of ​​the Herlang Public Health Center. It is suggested that the results of this study can be used as scientific reading material in the library and can also be used as reference material for students who examine the problem.